Flame-retardant corrugated paper and method for producing the same

By employing a flame-retardant composite retention medium and a moisture-resistant flame-retardant sealing layer in corrugated paper, the problems of unstable flame retardant retention and strength reduction in flame-retardant corrugated paper are solved, achieving simultaneous improvement in flame-retardant performance and mechanical properties.

CN123027770APending Publication Date: 2026-11-03KUNSHAN SUPERMIX PRINTING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611094314.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing flame-retardant corrugated paper has problems such as unstable flame retardant retention, reduced paperboard strength after flame retardant treatment, and insufficient retention of edge crush strength and adhesive strength after being exposed to moisture.

Method used

Flame-retardant face paper and core paper are prepared using pulp containing flame-retardant composite residues. A moisture-resistant and flame-retardant sealing layer is set on the outer surface of the face paper and the bonding area of ​​the corrugated core paper. Combined with a flame-retardant starch adhesive layer, a triple structure is formed, which includes flame retardancy within the fiber, moisture-resistant and flame-retardant sealing on the surface, and stable bonding of the corrugated core.

Benefits of technology

It improves flame retardancy, moisture resistance, edge crush strength retention rate and adhesive strength retention rate, ensuring the structural stability and overall performance of corrugated paper under humid and hot conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123027770A_ABST
    Figure CN123027770A_ABST
Patent Text Reader

Abstract

The application discloses a kind of fire-retardant corrugated paper and preparation method thereof, it is related to paper-based packaging material technical field, including sequentially bonded first fire-retardant face paper, fire-retardant corrugated core paper and second fire-retardant face paper;The first fire-retardant face paper, fire-retardant corrugated core paper and second fire-retardant face paper are all made by containing fire-retardant composite retention body paper pulp and are made;The side surface of the first fire-retardant face paper away from fire-retardant corrugated core paper, the side surface of the second fire-retardant face paper away from fire-retardant corrugated core paper and the corrugated peak bonding area of fire-retardant corrugated core paper are all provided with moisture-resistant fire-retardant sealing layer;The first fire-retardant face paper, fire-retardant corrugated core paper and second fire-retardant face paper are bonded by fire-retardant starch glue layer;Fire-retardant composite retention body is constructed by phosphorylated microfibrillated cellulose, ammonium polyphosphate, melamine phosphate, chitosan, phytic acid and magnesium aluminum hydrotalcite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of paper-based packaging materials technology, specifically to a flame-retardant corrugated paper and its preparation method. Background Technology

[0002] Corrugated cardboard is widely used in logistics and transportation packaging, home appliance packaging, electronic product packaging, warehousing and turnover packaging, and some industrial protective packaging due to its advantages such as light weight, low cost, good cushioning performance, and strong processing adaptability. Ordinary corrugated cardboard is mainly composed of cellulose fibers, which are flammable materials. It is easily ignited when exposed to open flames, high-temperature heat sources, or electrical sparks, and during combustion, flame spread, smoldering, and structural collapse are likely to occur. Therefore, in packaging scenarios with high fire safety requirements, flame-retardant modification of corrugated cardboard is necessary.

[0003] Existing flame-retardant corrugated paper is typically prepared using the following methods: First, flame retardants such as ammonium polyphosphate, phosphates, and borates are directly added to the pulp; second, flame-retardant liquid is coated onto the surface of the paper or paperboard; and third, flame-retardant fillers are added to the corrugated paperboard adhesive. While these methods can improve the flame retardancy of the paperboard to some extent, the following problems still exist: First, when flame retardants are directly added to the pulp, some inorganic salts or powdered flame retardants have insufficient bonding force with plant fibers and are easily lost during papermaking, dehydration, and drying, resulting in unstable flame retardant retention. Increasing the amount of flame retardant can also disrupt the hydrogen bonds between fibers, reducing the tensile strength, ring crush strength, and edge crush strength of the paper and corrugated paperboard. Second, simply coating the surface with flame-retardant liquid can cause the flame retardant to concentrate on the surface of the paperboard, resulting in weak bonding between the flame-retardant layer and the paper base. After folding, die-cutting, transportation friction, or exposure to moisture, the paperboard is prone to powdering, re-adhesion, or flame retardant migration, making it difficult to guarantee a long-term stable flame-retardant effect. Third, the flame-retardant properties of corrugated cardboard depend not only on the linerboard and core paper themselves, but also on the adhesive layer structure in the flute bonding area. Existing ordinary starch adhesives show a significant decrease in bonding strength after absorbing moisture; if the adhesive layer itself does not contribute to flame retardancy, the flute peaks are prone to delamination under flame, causing premature instability of the cardboard structure. Fourth, the inter-fiber bonding force decreases after the paper base material absorbs moisture, reducing the flute support capacity of the corrugated core paper and significantly decreasing the edge crush strength and adhesive strength retention rate. For flame-retardant corrugated paper, some hydrophilic phosphorus-nitrogen flame retardants further increase the cardboard's hygroscopicity, making it difficult to simultaneously achieve "improved flame-retardant properties" and "maintained mechanical properties and moisture resistance."

[0004] Therefore, it is necessary to provide a new flame-retardant corrugated paper and its preparation method, so that the flame retardant can be stably retained in the fiber network, and the structural stability of the paperboard under humid and hot conditions can be improved by the surface moisture-resistant flame-retardant sealing layer and flame-retardant adhesive layer, thereby solving the problems of easy moisture absorption, decreased edge crush strength and insufficient retention rate of flute peak bonding strength of the corrugated paper after flame retardant treatment. Summary of the Invention

[0005] In view of the shortcomings of the prior art, the purpose of this invention is to provide a flame-retardant corrugated paper and its preparation method to address the problems of unstable flame retardant retention, reduced paperboard strength after flame retardant treatment, and insufficient retention of edge crush strength and adhesive strength after moisture absorption in existing flame-retardant corrugated paper.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a flame-retardant corrugated paper, comprising a first flame-retardant facing paper, a flame-retardant corrugated core paper, and a second flame-retardant facing paper bonded together in sequence; The first flame-retardant face paper, the flame-retardant corrugated core paper, and the second flame-retardant face paper are all made from pulp containing flame-retardant composite residues; The first flame-retardant face paper is provided with a moisture-resistant flame-retardant sealing layer on the side surface away from the flame-retardant corrugated core paper, the second flame-retardant face paper is provided with a side surface away from the flame-retardant corrugated core paper, and the corrugated peak bonding area of ​​the flame-retardant corrugated core paper. The first flame-retardant face paper, the flame-retardant corrugated core paper, and the second flame-retardant face paper are bonded together by a flame-retardant starch adhesive layer.

[0007] The flame-retardant composite residue is prepared from the following raw materials on a dry basis: 100 parts phosphorylated microfibrillated cellulose, 60-160 parts ammonium polyphosphate, 15-70 parts melamine phosphate, 8-35 parts chitosan, 3-20 parts phytic acid, 5-45 parts magnesium aluminum hydrotalcite, and 500-2000 parts deionized water.

[0008] The moisture-resistant and flame-retardant sealing layer is prepared from the following raw materials on a dry basis: 100 parts of oxidized starch, 10-45 parts of polyvinyl alcohol, 15-70 parts of water-based silica sol, 2-12 parts of alkyl ketene dimer emulsion, 5-35 parts of phosphate starch, and 0.5-8 parts of crosslinking agent.

[0009] The flame-retardant starch adhesive layer is prepared from the following raw materials on a dry basis: 100 parts corn starch, 8-30 parts ammonium polyphosphate, 3-18 parts melamine cyanurate, 0.5-6 parts polyamide epichlorohydrin resin, 0-3 parts borate, 0.5-4 parts sodium hydroxide, and 250-600 parts deionized water.

[0010] Furthermore, in the first and second flame-retardant face paper, the dry basis addition amount of the flame-retardant composite residue is 4.0-12.0 wt% of the oven-dry fiber mass of the face paper; in the flame-retardant corrugated core paper, the dry basis addition amount of the flame-retardant composite residue is 7.0-20.0 wt% of the oven-dry fiber mass of the core paper.

[0011] Furthermore, the dry basis amount of the flame-retardant composite residue in the flame-retardant corrugated core paper is 1.2-2.5 times that in the first or second flame-retardant face paper.

[0012] Furthermore, the D50 particle size of the flame-retardant composite residue is 1.0-18.0 μm, the Zeta potential is +5 mV to +35 mV, and the mass ratio of phosphorus to nitrogen in the flame-retardant composite residue is 1:0.25-1.20.

[0013] Furthermore, the phosphorylated microfibrillated cellulose has a diameter of 20-800 nm, an aspect ratio of 20-200, and a phosphorus content of 0.3-3.5 wt%; the magnesium aluminum hydrotalcite is a plate-like magnesium aluminum hydrotalcite with an average plate diameter of 0.2-5.0 μm.

[0014] Furthermore, the dry coating amount of the moisture-resistant and flame-retardant sealing layer on the outer surfaces of the first and second flame-retardant facing papers is 1.5-8.0 g / m², and the dry coating amount of the moisture-resistant and flame-retardant sealing layer in the bonding area of ​​the flame-retardant corrugated core paper is 0.5-4.0 g / m².

[0015] Furthermore, the crosslinking agent is one or more of glyoxal, citric acid, zirconium ammonium carbonate, and polyamide epichlorohydrin resin; the dry adhesive weight of the flame-retardant starch adhesive layer is 3.0-12.0 g / m², and the flame-retardant starch adhesive layer is located in the contact area between the flute peak of the flame-retardant corrugated core paper and the first flame-retardant face paper and the second flame-retardant face paper.

[0016] This invention also provides a method for preparing flame-retardant corrugated paper, comprising the following steps: S1. Preparation of flame-retardant composite residue: Phosphorylated microfibrillated cellulose is added to deionized water and dispersed at 800-3000 r / min for 20-60 min to obtain a cellulose dispersion; ammonium polyphosphate, melamine phosphate and magnesium aluminum hydrotalcite are added to the cellulose dispersion and dispersed at 30-55℃ and 1000-5000 r / min for 30-120 min; then chitosan acidic solution and phytic acid are added and reacted at pH 4.5-6.2 for 30-120 min to obtain a flame-retardant composite residue dispersion; S2. Preparation of flame-retardant face paper and flame-retardant corrugated core paper: One or more of waste paper pulp, softwood pulp, and hardwood pulp are diluted with water and beaten to 25-45°SR to obtain pulp slurry; the flame-retardant composite residue dispersion obtained in step S1, cationic starch, polyamide epichlorohydrin resin and sizing agent are added to the pulp slurry, and after mixing, the mixture is formed, pressed and dried to obtain the first flame-retardant face paper, the second flame-retardant face paper and the flame-retardant corrugated core paper, respectively. S3. Preparation of moisture-resistant and flame-retardant sealing liquid: Add oxidized starch to deionized water and gelatinize at 85-98℃ for 20-60 min. After cooling to 50-75℃, add polyvinyl alcohol, water-based silica sol, phosphate starch, alkyl ketene dimer emulsion and crosslinking agent, and stir for 20-80 min to obtain moisture-resistant and flame-retardant sealing liquid. S4. Surface sealing treatment: The moisture-resistant flame-retardant sealing liquid obtained in step S3 is applied to the outer surface of the first flame-retardant face paper and the second flame-retardant face paper, and applied or transferred to the corrugated peak bonding area of ​​the flame-retardant corrugated core paper. After hot air drying, a moisture-resistant flame-retardant sealing layer is formed. S5. Preparation of flame-retardant starch adhesive: Add corn starch to deionized water, add sodium hydroxide to gelatinize, then add ammonium polyphosphate, melamine cyanurate and polyamide epichlorohydrin resin, stir for 20-90 minutes to obtain flame-retardant starch adhesive. S6. Corrugated Forming and Composite: The flame-retardant corrugated core paper processed in step S4 is hot-pressed by a corrugated roller, and the flame-retardant starch adhesive obtained in step S5 is applied to its flute peaks. Then it is laminated with the first flame-retardant face paper and the second flame-retardant face paper respectively. After pressing, drying, shaping and humidification, the flame-retardant corrugated paper is obtained.

[0017] Further, in step S2, the amount of cationic starch added is 0.5-2.5 wt% of the oven-dry fiber mass, the amount of polyamide epichlorohydrin resin added is 0.2-1.5 wt% of the oven-dry fiber mass, and the sizing agent is one or more of alkyl ketene dimer, alkenyl succinic anhydride, or rosin gum, and the amount of the sizing agent added is 0.05-0.50 wt% of the oven-dry fiber mass.

[0018] Further, in step S4, the hot air drying temperature is 80-130℃ and the drying time is 20-180s; in step S6, the corrugated roll temperature is 140-190℃ and the pressing pressure is 0.2-0.8MPa. After drying and shaping, the obtained flame-retardant corrugated paper is conditioned at a temperature of 20-30℃ and a relative humidity of 45-65% for 12-48h.

[0019] Compared with existing technologies, this invention provides a flame-retardant corrugated paper and its preparation method, which has the following beneficial effects: This invention constructs a flame-retardant composite residue using phosphorylated microfibrillated cellulose, ammonium polyphosphate, melamine phosphate, chitosan, phytic acid, and magnesium aluminum hydrotalcite. Phosphorylated microfibrillated cellulose has a dual function of reinforcing the fiber network and forming flame-retardant char; ammonium polyphosphate and melamine phosphate provide acid and gas sources; chitosan and phytic acid form a polyelectrolyte bond structure, improving the bonding stability between the flame retardant and the fiber system; magnesium aluminum hydrotalcite promotes the densification of the heat-insulating char layer during combustion. Therefore, the flame-retardant composite residue can improve flame retardancy while reducing the damage to the inter-fiber bonding caused by ordinary powdered flame retardants.

[0020] This invention employs a differentiated flame-retardant retention design between the face paper and the corrugated core paper, enabling the flame-retardant corrugated core paper, which bears the corrugated support and flame channel function, to have a higher content of flame-retardant composite residue, while the face paper maintains a moderate amount of flame retardant, thereby achieving a balance between flame-retardant performance and edge crush strength.

[0021] This invention provides a moisture-resistant and flame-retardant sealing layer on the outer surface of the face paper and at the bonding area of ​​the corrugated core paper. Oxidized starch, polyvinyl alcohol, and phosphate starch provide film-forming properties and flame-retardant assistance; aqueous silica sol improves thermal stability and surface density; alkyl ketene dimer emulsion reduces surface water absorption; and a crosslinking agent improves the coating's water resistance stability under humid and hot conditions. This structure can reduce the strength degradation of flame-retardant corrugated paper after moisture absorption.

[0022] This invention introduces flame-retardant components into the starch adhesive layer and improves the wet strength of the adhesive layer through polyamide epichlorohydrin resin, making the corrugated peak bonding area less prone to premature delamination under moisture and flame conditions, which helps maintain the overall structural integrity of the corrugated cardboard.

[0023] This invention forms a triple structure consisting of "fiber-retardant composite retention body, surface moisture-resistant flame-retardant sealing layer, and flute peak flame-retardant starch adhesive layer". The three components respectively act to retard the flame inside the paper, provide surface moisture resistance and barrier, and stabilize the flute peak adhesion, thereby simultaneously improving the flame retardant performance, moisture resistance, edge crush strength retention rate and adhesive strength retention rate, and having a synergistic effect. Attached Figure Description

[0024] Figure 1 This is a scanning electron microscope image of the flame-retardant composite residue obtained in Example 4 loaded on the surface of pulp fibers; Figure 2 This is a cross-sectional scanning electron microscope image of the moisture-resistant and flame-retardant sealing layer on the surface of the flame-retardant corrugated paper obtained in Example 4. Detailed Implementation

[0025] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0026] Please see Figures 1-2 This invention provides a technical solution for flame-retardant corrugated paper and its preparation method: The phosphorylated microfibrillated cellulose used in the examples was obtained from bleached softwood pulp through phosphorylation modification and high-pressure homogenization. It had a diameter of 20-800 nm, an aspect ratio of 20-200, and a phosphorus content of 0.3-3.5 wt%. The magnesium aluminum hydrotalcite was in flake form with an average flake diameter of 0.2-5.0 μm. The basis weight of the linerboard was controlled at 170±5 g / m², and the basis weight of the corrugated core paper was controlled at 120±5 g / m², resulting in a three-layer B-flute corrugated cardboard.

[0027] Example 1: Preparation of a flame-retardant corrugated paper. Preparation of flame-retardant composite residues Based on dry weight, take 100 parts phosphorylated microfibrillated cellulose, 60 parts ammonium polyphosphate, 15 parts melamine phosphate, 8 parts chitosan, 3 parts phytic acid, 5 parts magnesium aluminum hydrotalcite, and 500 parts deionized water.

[0028] Phosphorylated microfibrillated cellulose was added to deionized water and dispersed at 800 rpm for 20 min to obtain a cellulose dispersion. Ammonium polyphosphate, melamine phosphate, and magnesium aluminum hydrotalcite were added to the cellulose dispersion, and the mixture was dispersed at 30°C and 1000 rpm for 30 min. Subsequently, an acidic chitosan solution and phytic acid were added to adjust the pH to 4.5, and the reaction was allowed to proceed for 30 min to obtain a flame-retardant composite residue dispersion. The resulting flame-retardant composite residue had a D50 particle size of 16.8 μm and a Zeta potential of +6.2 mV.

[0029] Preparation of flame-retardant face paper and flame-retardant corrugated core paper Softwood pulp and hardwood pulp were mixed at a mass ratio of 30:70, diluted with water, and beaten to 25°SR to obtain pulp stock. A flame-retardant composite residue dispersion was added to the pulp stock used for face paper, with the dry basis addition amount of the flame-retardant composite residue being 4.0 wt% of the oven-dry fiber mass of the face paper; a flame-retardant composite residue dispersion was added to the pulp stock used for corrugated core paper, with the dry basis addition amount of the flame-retardant composite residue being 7.0 wt% of the oven-dry fiber mass of the core paper.

[0030] Subsequently, 0.5 wt% cationic starch, 0.2 wt% polyamide epichlorohydrin resin and 0.05 wt% alkyl ketene dimer were added respectively. After being mixed evenly, the mixture was formed, pressed and dried to obtain the first flame-retardant face paper, the second flame-retardant face paper and the flame-retardant corrugated core paper.

[0031] Preparation of moisture-resistant and flame-retardant sealing liquid Based on dry weight, take 100 parts of oxidized starch, 10 parts of polyvinyl alcohol, 15 parts of aqueous silica sol, 2 parts of alkyl ketene dimer emulsion, 5 parts of phosphate starch, and 0.5 parts of glyoxal. Add the oxidized starch to deionized water and gelatinize at 85°C for 20 min. After cooling to 50°C, add polyvinyl alcohol, aqueous silica sol, phosphate starch, alkyl ketene dimer emulsion, and glyoxal, and stir for 20 min to obtain a moisture-resistant and flame-retardant sealing liquid.

[0032] A moisture-resistant flame-retardant sealing liquid was applied to the outer surfaces of the first and second flame-retardant facing papers, with a dry coating amount of 1.5 g / m² for both. Simultaneously, the moisture-resistant flame-retardant sealing liquid was transferred and applied to the corrugated bonding area of ​​the flame-retardant corrugated core paper, with a dry coating amount of 0.5 g / m². The paper was then dried under 80°C hot air for 180 seconds to form a moisture-resistant flame-retardant sealing layer.

[0033] Preparation of flame-retardant starch adhesive and corrugated composite Based on dry weight, take 100 parts corn starch, 8 parts ammonium polyphosphate, 3 parts melamine cyanurate, 0.5 parts polyamide epichlorohydrin resin, 0.5 parts sodium hydroxide, and 250 parts deionized water. Add the corn starch to the deionized water, add sodium hydroxide to gelatinize, then add ammonium polyphosphate, melamine cyanurate, and polyamide epichlorohydrin resin, and stir for 20 minutes to obtain a flame-retardant starch adhesive.

[0034] The treated flame-retardant corrugated core paper was hot-pressed by a corrugated roll at a temperature of 140°C. Flame-retardant starch adhesive was applied to the corrugation peaks with a dry adhesive amount of 3.0 g / m². Subsequently, it was laminated with the first and second flame-retardant face papers respectively, pressed, dried and shaped under a pressure of 0.2 MPa, and then conditioned at 20°C and 45% relative humidity for 12 hours to obtain flame-retardant corrugated paper.

[0035] Example 2, Preparation of flame-retardant composite residue Based on dry weight, take 100 parts phosphorylated microfibrillated cellulose, 110 parts ammonium polyphosphate, 40 parts melamine phosphate, 20 parts chitosan, 10 parts phytic acid, 25 parts magnesium aluminum hydrotalcite, and 1200 parts deionized water.

[0036] Phosphorylated microfibrillated cellulose was added to deionized water and dispersed at 1800 r / min for 40 min to obtain a cellulose dispersion. Ammonium polyphosphate, melamine phosphate, and magnesium aluminum hydrotalcite were added to the cellulose dispersion, and the mixture was dispersed at 42℃ and 3000 r / min for 70 min. Subsequently, an acidic chitosan solution and phytic acid were added to adjust the pH to 5.4, and the reaction was carried out for 75 min to obtain a flame-retardant composite residue dispersion. The resulting flame-retardant composite residue had a D50 particle size of 7.6 μm and a Zeta potential of +18.5 mV.

[0037] Preparation of flame-retardant face paper and flame-retardant corrugated core paper Waste paper pulp, softwood pulp, and hardwood pulp were mixed in a mass ratio of 50:20:30, diluted with water, and beaten to 35°SR to obtain pulp stock. A flame-retardant composite residue dispersion was added to the pulp stock used for face paper, with the dry basis addition amount of the flame-retardant composite residue being 8.0 wt% of the oven-dry fiber mass of the face paper; a flame-retardant composite residue dispersion was added to the pulp stock used for corrugated core paper, with the dry basis addition amount of the flame-retardant composite residue being 14.0 wt% of the oven-dry fiber mass of the core paper.

[0038] Subsequently, 1.5 wt% cationic starch, 0.8 wt% polyamide epichlorohydrin resin and 0.25 wt% alkyl ketene dimer were added respectively. After being mixed evenly, the mixture was formed, pressed and dried to obtain the first flame-retardant face paper, the second flame-retardant face paper and the flame-retardant corrugated core paper.

[0039] Preparation of moisture-resistant and flame-retardant sealing liquid Based on dry weight, take 100 parts of oxidized starch, 28 parts of polyvinyl alcohol, 42 parts of aqueous silica sol, 7 parts of alkyl ketene dimer emulsion, 20 parts of phosphate starch, and 4 parts of citric acid. Add the oxidized starch to deionized water and gelatinize at 92℃ for 40 min. After cooling to 62℃, add polyvinyl alcohol, aqueous silica sol, phosphate starch, alkyl ketene dimer emulsion, and citric acid, and stir for 50 min to obtain a moisture-resistant and flame-retardant sealing liquid.

[0040] A moisture-resistant flame-retardant sealing liquid was applied to the outer surfaces of the first and second flame-retardant facing papers, with a dry coating amount of 4.5 g / m² for both. Simultaneously, the moisture-resistant flame-retardant sealing liquid was transferred and applied to the corrugated peak bonding area of ​​the flame-retardant corrugated core paper, with a dry coating amount of 2.0 g / m². The paper was then dried under hot air conditions at 105°C for 80 seconds to form a moisture-resistant flame-retardant sealing layer.

[0041] Preparation of flame-retardant starch adhesive and corrugated composite Based on dry weight, take 100 parts corn starch, 18 parts ammonium polyphosphate, 10 parts melamine cyanurate, 3 parts polyamide epichlorohydrin resin, 1.5 parts borate, 2 parts sodium hydroxide, and 420 parts deionized water. Add the corn starch to the deionized water, add sodium hydroxide to gelatinize, then add ammonium polyphosphate, melamine cyanurate, polyamide epichlorohydrin resin, and borate, and stir for 55 minutes to obtain a flame-retardant starch adhesive.

[0042] The treated flame-retardant corrugated core paper was hot-pressed by a corrugated roll at a temperature of 165°C. Flame-retardant starch adhesive was applied to the corrugation peaks with a dry adhesive amount of 7.5 g / m². Subsequently, it was laminated with the first and second flame-retardant face papers respectively, pressed, dried and shaped under a pressure of 0.5 MPa, and then conditioned for 24 hours at a temperature of 25°C and a relative humidity of 55% to obtain flame-retardant corrugated paper.

[0043] Example 3, Preparation of flame-retardant composite residue Based on dry weight, take 100 parts phosphorylated microfibrillated cellulose, 160 parts ammonium polyphosphate, 70 parts melamine phosphate, 35 parts chitosan, 20 parts phytic acid, 45 parts magnesium aluminum hydrotalcite, and 2000 parts deionized water.

[0044] Phosphorylated microfibrillated cellulose was added to deionized water and dispersed at 3000 r / min for 60 min to obtain a cellulose dispersion. Ammonium polyphosphate, melamine phosphate, and magnesium aluminum hydrotalcite were added to the cellulose dispersion, and the mixture was dispersed at 55℃ and 5000 r / min for 120 min. Subsequently, an acidic chitosan solution and phytic acid were added to adjust the pH to 6.2, and the reaction was carried out for 120 min to obtain a flame-retardant composite residue dispersion. The obtained flame-retardant composite residue had a D50 particle size of 2.4 μm and a Zeta potential of +31.6 mV.

[0045] Preparation of flame-retardant face paper and flame-retardant corrugated core paper Waste paper pulp and softwood pulp were mixed at a mass ratio of 70:30, diluted with water, and beaten to 45°SR to obtain pulp stock. A flame-retardant composite residue dispersion was added to the pulp stock used for face paper, with the dry basis addition amount of the flame-retardant composite residue being 12.0 wt% of the oven-dry fiber mass of the face paper; a flame-retardant composite residue dispersion was added to the pulp stock used for corrugated core paper, with the dry basis addition amount of the flame-retardant composite residue being 20.0 wt% of the oven-dry fiber mass of the core paper.

[0046] Subsequently, 2.5 wt% cationic starch, 1.5 wt% polyamide epichlorohydrin resin and 0.50 wt% alkyl ketene dimer were added respectively. After being mixed evenly, the mixture was formed, pressed and dried to obtain the first flame-retardant face paper, the second flame-retardant face paper and the flame-retardant corrugated core paper.

[0047] Preparation of moisture-resistant and flame-retardant sealing liquid Based on dry weight, take 100 parts of oxidized starch, 45 parts of polyvinyl alcohol, 70 parts of aqueous silica sol, 12 parts of alkyl ketene dimer emulsion, 35 parts of phosphate starch, and 8 parts of zirconium carbonate. Add the oxidized starch to deionized water and gelatinize at 98°C for 60 min. After cooling to 75°C, add polyvinyl alcohol, aqueous silica sol, phosphate starch, alkyl ketene dimer emulsion, and zirconium carbonate, and stir for 80 min to obtain a moisture-resistant and flame-retardant sealing liquid.

[0048] A moisture-resistant flame-retardant sealing liquid was applied to the outer surfaces of the first and second flame-retardant facing papers, with a dry coating amount of 8.0 g / m² for both. Simultaneously, the moisture-resistant flame-retardant sealing liquid was transferred and applied to the corrugated peak bonding area of ​​the flame-retardant corrugated core paper, with a dry coating amount of 4.0 g / m². The paper was then dried under hot air conditions at 130°C for 20 seconds to form a moisture-resistant flame-retardant sealing layer.

[0049] Preparation of flame-retardant starch adhesive and corrugated composite Based on dry weight, take 100 parts corn starch, 30 parts ammonium polyphosphate, 18 parts melamine cyanurate, 6 parts polyamide epichlorohydrin resin, 3 parts borate, 4 parts sodium hydroxide, and 600 parts deionized water. Add the corn starch to the deionized water, add sodium hydroxide to gelatinize, then add ammonium polyphosphate, melamine cyanurate, polyamide epichlorohydrin resin, and borate, and stir for 90 minutes to obtain a flame-retardant starch adhesive.

[0050] The treated flame-retardant corrugated core paper was hot-pressed by a corrugated roll at a temperature of 190°C. Flame-retardant starch adhesive was applied to the corrugation peaks with a dry adhesive amount of 12.0 g / m². Subsequently, it was laminated with the first and second flame-retardant face papers respectively, pressed, dried and shaped under a pressure of 0.8 MPa, and then conditioned at 30°C and 65% relative humidity for 48 hours to obtain flame-retardant corrugated paper.

[0051] Example 4, Preparation of flame-retardant composite residue Based on dry weight, take 100 parts phosphorylated microfibrillated cellulose, 125 parts ammonium polyphosphate, 45 parts melamine phosphate, 18 parts chitosan, 12 parts phytic acid, 22 parts magnesium aluminum hydrotalcite, and 1300 parts deionized water.

[0052] Phosphorylated microfibrillated cellulose was added to deionized water and dispersed at 2200 r / min for 45 min to obtain a cellulose dispersion. Ammonium polyphosphate, melamine phosphate, and magnesium aluminum hydrotalcite were added to the cellulose dispersion, and the mixture was dispersed at 45℃ and 3500 r / min for 80 min. Subsequently, an acidic chitosan solution and phytic acid were added to adjust the pH to 5.6, and the reaction was carried out for 80 min to obtain a flame-retardant composite residue dispersion. The obtained flame-retardant composite residue had a D50 particle size of 6.2 μm and a Zeta potential of +21.4 mV.

[0053] Preparation of flame-retardant face paper and flame-retardant corrugated core paper Waste paper pulp, softwood pulp, and hardwood pulp were mixed in a mass ratio of 55:25:20, diluted with water, and beaten to 38°SR to obtain pulp stock. A flame-retardant composite residue dispersion was added to the pulp stock used for face paper, with the dry basis addition amount of the flame-retardant composite residue being 7.5 wt% of the oven-dry fiber mass of the face paper; a flame-retardant composite residue dispersion was added to the pulp stock used for corrugated core paper, with the dry basis addition amount of the flame-retardant composite residue being 12.5 wt% of the oven-dry fiber mass of the core paper.

[0054] Subsequently, 1.6 wt% cationic starch, 0.9 wt% polyamide epichlorohydrin resin and 0.28 wt% alkyl ketene dimer were added respectively. After being mixed evenly, the mixture was formed, pressed and dried to obtain the first flame-retardant face paper, the second flame-retardant face paper and the flame-retardant corrugated core paper.

[0055] Preparation of moisture-resistant and flame-retardant sealing liquid Based on dry weight, take 100 parts of oxidized starch, 30 parts of polyvinyl alcohol, 45 parts of aqueous silica sol, 6 parts of alkyl ketene dimer emulsion, 18 parts of phosphate starch, and 3 parts of polyamide epichlorohydrin resin. Add the oxidized starch to deionized water and gelatinize at 92°C for 45 min. After cooling to 65°C, add polyvinyl alcohol, aqueous silica sol, phosphate starch, alkyl ketene dimer emulsion, and polyamide epichlorohydrin resin, and stir for 55 min to obtain a moisture-resistant and flame-retardant sealing liquid.

[0056] A moisture-resistant flame-retardant sealing liquid was applied to the outer surfaces of the first and second flame-retardant facing papers, with a dry coating amount of 4.0 g / m² for both. Simultaneously, the moisture-resistant flame-retardant sealing liquid was transferred and applied to the corrugated peak bonding area of ​​the flame-retardant corrugated core paper, with a dry coating amount of 1.8 g / m². The paper was then dried under hot air conditions at 110°C for 70 seconds to form a moisture-resistant flame-retardant sealing layer.

[0057] Preparation of flame-retardant starch adhesive and corrugated composite Based on dry weight, take 100 parts corn starch, 20 parts ammonium polyphosphate, 9 parts melamine cyanurate, 3.5 parts polyamide epichlorohydrin resin, 1.2 parts borate, 2.2 parts sodium hydroxide, and 430 parts deionized water. Add corn starch to deionized water, add sodium hydroxide to gelatinize, then add ammonium polyphosphate, melamine cyanurate, polyamide epichlorohydrin resin, and borate, and stir for 60 minutes to obtain flame-retardant starch adhesive.

[0058] The treated flame-retardant corrugated core paper is hot-pressed by a corrugated roll at a temperature of 170°C. Flame-retardant starch adhesive is applied to the corrugation peaks with a dry adhesive amount of 6.5 g / m². Subsequently, it is laminated with the first and second flame-retardant face papers respectively, pressed, dried and shaped under a pressure of 0.45 MPa, and conditioned for 24 hours at a temperature of 25°C and a relative humidity of 55% to obtain flame-retardant corrugated paper.

[0059] Comparative Example 1: The flame-retardant composite residue was replaced with an equal dry basis mass of a common powder flame retardant mixture. This common powder flame retardant mixture was directly mixed from ammonium polyphosphate, melamine phosphate, and magnesium aluminum hydrotalcite in the same mass ratio as in Example 4, and did not contain phosphorylated microfibrillated cellulose, chitosan, or phytic acid composite structures. Other conditions were the same as in Example 4.

[0060] Comparative Example 2: No moisture-resistant flame-retardant sealing liquid coating treatment was performed; that is, no moisture-resistant flame-retardant sealing layer was applied to the outer surfaces of the first and second flame-retardant face papers, or to the bonding area of ​​the flute peaks of the flame-retardant corrugated core paper. Other conditions were the same as in Example 4.

[0061] Comparative Example 3: The flame-retardant starch adhesive was replaced with a regular starch adhesive. The regular starch adhesive was prepared from 100 parts corn starch, 2.2 parts sodium hydroxide, and 430 parts deionized water, without the addition of ammonium polyphosphate, melamine cyanurate, polyamide epichlorohydrin resin, or borate. Other conditions were the same as in Example 4.

[0062] Comparative Example 4: Magnesium aluminum hydrotalcite was not added to the flame-retardant composite residue, while other flame-retardant composite residue components and their amounts remained unchanged. Other conditions were the same as in Example 4.

[0063] In Comparative Example 5, the dry basis addition amount of the flame-retardant composite residue in the first flame-retardant face paper, the second flame-retardant face paper, and the flame-retardant corrugated core paper was 10.0 wt%, and the differentiated flame-retardant residue design with the corrugated core paper being higher than that of the face paper was not adopted. Other conditions were the same as in Example 4.

[0064] Performance testing Before testing, all flame-retardant corrugated papers obtained in the examples and comparative examples were subjected to sample treatment and test environment equilibration under the standard atmospheric conditions specified in GB / T 10739-2023.

[0065] Combustion performance test The combustion performance was tested according to GB / T 14656-2009 "Test Method for Combustion Performance of Flame Retardant Paper and Paperboard", and the afterflame time, smoldering time and char length were recorded. Five samples were tested for each group of samples, and the average value was taken.

[0066] Edge pressure strength test The edge crush strength of corrugated board was determined according to GB / T 6546-2021 "Determination of Edge Crush Strength of Corrugated Board", with the unit being N / m. Ten samples were tested for each group, and the average value was taken.

[0067] Bursting strength test The bursting strength of corrugated board was determined according to GB / T 6545-1998 "Determination of Bursting Strength of Corrugated Board", with the unit being kPa. Ten samples were tested in each group, and the average value was taken.

[0068] Adhesion strength test The bonding strength of corrugated board was determined according to GB / T 6548-2011 "Determination of Bonding Strength of Corrugated Board", with the unit being N / m flute. Ten samples were tested for each group, and the average value was taken.

[0069] Water absorption test The water absorption value of the outer surface of the paperboard was determined according to GB / T 1540-2002 "Determination of water absorption of paper and paperboard (Cobb method)", with the unit being g / m². Five samples were tested for each group of samples, and the average value was taken.

[0070] Strength retention rate test after damp heat treatment The samples were treated at 38℃ and 90% relative humidity for 24 hours, then equilibrated under standard atmospheric conditions specified in GB / T 10739-2023 for 4 hours. Edge crush strength and adhesive strength were then tested according to GB / T 6546-2021 and GB / T 6548-2011, respectively. The retention rate was calculated using the following formula: Edge compressive strength retention rate / % = Edge compressive strength after damp heat treatment / Edge compressive strength before damp heat treatment × 100%.

[0071] Adhesion strength retention rate / % = Adhesion strength after wet heat treatment / Adhesion strength before wet heat treatment × 100%.

[0072] Table 1

[0073] Table 2

[0074] As shown in Tables 1 and 2, in Comparative Example 1, replacing the flame-retardant composite retainer with a mixture of ordinary powdered flame retardants significantly increased the afterflame time, smoldering time, and char length, while decreasing the edge crush strength and edge crush strength retention rate after wet heat. This indicates that simply adding flame-retardant powder directly to the pulp, while providing some flame retardancy, results in insufficient bonding with the fiber network, easily disrupting the paper fiber bond and reducing wet heat stability. In this invention, the composite retainer structure formed by phosphorylated microfibrillated cellulose, chitosan, and phytic acid improves the stable distribution of the flame retardant in the fiber system while mitigating the damage to the mechanical properties of the paperboard caused by the flame retardant.

[0075] Comparative Example 2, without a moisture-resistant and flame-retardant sealing layer, showed a significantly increased Cobb60 water absorption value, and a marked decrease in edge crush strength retention and bond strength retention after humid heat. This indicates that the moisture-resistant and flame-retardant sealing layer not only provides surface flame-retardant assistance but, more importantly, reduces the rate at which moisture penetrates the cardboard interior and the corrugated bonding area, thereby improving structural retention under humid heat conditions.

[0076] In Comparative Example 3, replacing the flame-retardant starch adhesive with ordinary starch adhesive did not significantly change the combustion performance, but the bonding strength and the retention rate of bonding strength after damp heat decreased significantly. This indicates that the overall flame-retardant and load-bearing performance of corrugated cardboard depends not only on the paper sheet itself but also on the wet strength and thermal stability of the flute adhesive layer. The flame-retardant starch adhesive layer of this invention can improve the stability of the flute bonding area under moisture and heat conditions.

[0077] In Comparative Example 4, omitting the magnesium-aluminum hydrotalcite resulted in minimal changes in edge compressive strength and bond strength, but significantly increased afterflame time, smoldering time, and char length. This indicates that the magnesium-aluminum hydrotalcite primarily enhances flame retardancy by promoting densification of the insulating char layer, reducing char layer cracking, and delaying heat transfer, exhibiting a synergistic flame retardant effect with the phosphorus-nitrogen flame retardant system.

[0078] Comparative Example 5 does not employ a differentiated flame-retardant retention design where the corrugated core paper has a higher content than the face paper; instead, the amount of flame-retardant composite retention material added to both the face paper and core paper is the same. This sample exhibits weaker flame-retardant performance and lower edge crush strength than Example 4. This demonstrates that in a corrugated structure, the core paper is both a crucial component for flame propagation along the flute grooves and a key component for edge crush support. This invention, by enabling the flame-retardant corrugated core paper to have a higher content of flame-retardant composite retention material than the face paper, while simultaneously controlling the amount added to the face paper, achieves a more reasonable structural distribution between flame retardancy and strength.

[0079] Figure 1 In Example 4, the flame-retardant composite residue obtained can be effectively loaded onto the surface of pulp fibers and the fiber overlap area. From the microscopic morphology level, this invention supports the flame-retardant composite residue in improving the retention stability of flame retardants, reducing the migration of free flame-retardant powders, and reducing the adverse effects of flame-retardant treatment on the strength of paperboard.

[0080] Figure 2 In Example 4, a moisture-resistant and flame-retardant sealing layer was indeed formed on the outer surface of the flame-retardant corrugated paper, and this sealing layer had a good interfacial bonding state with the paper base fiber layer. Microstructurally, the moisture-resistant and flame-retardant sealing layer can reduce the number of open pores on the paperboard surface, slow down the penetration of moisture into the paper base, and improve the Cobb water absorption performance, edge crush strength retention rate after wet heat, and adhesive strength retention rate after wet heat of the flame-retardant corrugated paper.

[0081] In summary, the flame-retardant corrugated paper of this invention, through the combination of "flame-retardant composite retention layer, moisture-resistant flame-retardant sealing layer, and flame-retardant starch adhesive layer," does not simply increase the amount of flame retardant, but rather constructs functional structures within the paper sheet, on the paperboard surface, and in the corrugation bonding area. This combination can simultaneously reduce afterflame time, smoldering time, and char length, reduce Cobb water absorption value, and improve edge crush strength retention and adhesive strength retention after wet heat. Single-factor changes in each comparative example lead to a significant decrease in at least one key performance characteristic, demonstrating a synergistic effect among the various technical features of this invention and effectively solving the technical problem of decreased strength and moisture resistance after flame-retardant modification of flame-retardant corrugated paper.

[0082] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions, and alterations can be made to these embodiments without departing from the principles and spirit of the invention. The scope of protection of the invention is defined by the claims and their equivalents.

Claims

1. A flame-retardant corrugated paper, characterized in that, It includes a first flame-retardant face paper, a flame-retardant corrugated core paper, and a second flame-retardant face paper that are bonded together in sequence. The first flame-retardant face paper, the flame-retardant corrugated core paper, and the second flame-retardant face paper are all made from pulp containing flame-retardant composite adhesives; The first flame-retardant face paper is provided with a moisture-resistant flame-retardant sealing layer on the side surface away from the flame-retardant corrugated core paper, the second flame-retardant face paper is provided with a side surface away from the flame-retardant corrugated core paper, and the corrugated peak bonding area of ​​the flame-retardant corrugated core paper. The first flame-retardant face paper, the flame-retardant corrugated core paper, and the second flame-retardant face paper are bonded together by a flame-retardant starch adhesive layer. The flame-retardant composite residue is prepared from the following raw materials on a dry basis: 100 parts phosphorylated microfibrillated cellulose, 60-160 parts ammonium polyphosphate, 15-70 parts melamine phosphate, 8-35 parts chitosan, 3-20 parts phytic acid, 5-45 parts magnesium aluminum hydrotalcite, and 500-2000 parts deionized water. The moisture-resistant and flame-retardant sealing layer is prepared from the following raw materials on a dry basis: 100 parts of oxidized starch, 10-45 parts of polyvinyl alcohol, 15-70 parts of water-based silica sol, 2-12 parts of alkyl ketene dimer emulsion, 5-35 parts of phosphate starch and 0.5-8 parts of crosslinking agent. The flame-retardant starch adhesive layer is prepared from the following raw materials on a dry basis: 100 parts corn starch, 8-30 parts ammonium polyphosphate, 3-18 parts melamine cyanurate, 0.5-6 parts polyamide epichlorohydrin resin, 0-3 parts borate, 0.5-4 parts sodium hydroxide, and 250-600 parts deionized water.

2. The flame-retardant corrugated paper according to claim 1, characterized in that, In the first and second flame-retardant face paper, the dry basis addition amount of the flame-retardant composite residue is 4.0-12.0 wt% of the oven-dry fiber mass of the face paper; in the flame-retardant corrugated core paper, the dry basis addition amount of the flame-retardant composite residue is 7.0-20.0 wt% of the oven-dry fiber mass of the core paper.

3. The flame-retardant corrugated paper according to claim 2, characterized in that, The dry basis amount of the flame-retardant composite residue in the flame-retardant corrugated core paper is 1.2-2.5 times that in the first or second flame-retardant face paper.

4. The flame-retardant corrugated paper according to claim 1, characterized in that, The flame-retardant composite residue has a D50 particle size of 1.0-18.0 μm, a Zeta potential of +5 mV to +35 mV, and a mass ratio of phosphorus to nitrogen in the flame-retardant composite residue of 1:0.25-1.

20.

5. The flame-retardant corrugated paper according to claim 1, characterized in that, The phosphorylated microfibrillated cellulose has a diameter of 20-800 nm, an aspect ratio of 20-200, and a phosphorus content of 0.3-3.5 wt%. The magnesium aluminum hydrotalcite is a plate-like magnesium aluminum hydrotalcite with an average plate diameter of 0.2-5.0 μm.

6. The flame-retardant corrugated paper according to claim 1, characterized in that, The dry coating amount of the moisture-resistant and flame-retardant sealing layer on the outer surfaces of the first and second flame-retardant facing papers is 1.5-8.0 g / m², and the dry coating amount of the moisture-resistant and flame-retardant sealing layer in the bonding area of ​​the flute peaks of the flame-retardant corrugated core paper is 0.5-4.0 g / m².

7. The flame-retardant corrugated paper according to claim 1, characterized in that, The crosslinking agent is one or more of glyoxal, citric acid, zirconium ammonium carbonate, and polyamide epichlorohydrin resin; the dry adhesive content of the flame-retardant starch adhesive layer is 3.0-12.0 g / m², and the flame-retardant starch adhesive layer is located in the contact area between the flute peak of the flame-retardant corrugated core paper and the first flame-retardant face paper and the second flame-retardant face paper.

8. A method for preparing flame-retardant corrugated paper as described in any one of claims 1-7, characterized in that, Includes the following steps: S1. Preparation of flame-retardant composite residue: Phosphorylated microfibrillated cellulose is added to deionized water and dispersed at 800-3000 r / min for 20-60 min to obtain a cellulose dispersion; ammonium polyphosphate, melamine phosphate and magnesium aluminum hydrotalcite are added to the cellulose dispersion and dispersed at 30-55℃ and 1000-5000 r / min for 30-120 min; then chitosan acidic solution and phytic acid are added and reacted at pH 4.5-6.2 for 30-120 min to obtain a flame-retardant composite residue dispersion; S2. Preparation of flame-retardant face paper and flame-retardant corrugated core paper: One or more of waste paper pulp, softwood pulp, and hardwood pulp are diluted with water and beaten to 25-45°SR to obtain pulp slurry; the flame-retardant composite residue dispersion obtained in step S1, cationic starch, polyamide epichlorohydrin resin and sizing agent are added to the pulp slurry, and after mixing, the mixture is formed, pressed and dried to obtain the first flame-retardant face paper, the second flame-retardant face paper and the flame-retardant corrugated core paper, respectively. S3. Preparation of moisture-resistant and flame-retardant sealing liquid: Add oxidized starch to deionized water and gelatinize at 85-98℃ for 20-60 min. After cooling to 50-75℃, add polyvinyl alcohol, water-based silica sol, phosphate starch, alkyl ketene dimer emulsion and crosslinking agent, and stir for 20-80 min to obtain moisture-resistant and flame-retardant sealing liquid. S4. Surface sealing treatment: The moisture-resistant flame-retardant sealing liquid obtained in step S3 is applied to the outer surface of the first flame-retardant face paper and the second flame-retardant face paper, and applied or transferred to the corrugated peak bonding area of ​​the flame-retardant corrugated core paper. After hot air drying, a moisture-resistant flame-retardant sealing layer is formed. S5. Preparation of flame-retardant starch adhesive: Add corn starch to deionized water, add sodium hydroxide to gelatinize, then add ammonium polyphosphate, melamine cyanurate and polyamide epichlorohydrin resin, stir for 20-90 minutes to obtain flame-retardant starch adhesive. S6. Corrugated Forming and Composite: The flame-retardant corrugated core paper processed in step S4 is hot-pressed by a corrugated roller, and the flame-retardant starch adhesive obtained in step S5 is applied to its flute peaks. Then it is laminated with the first flame-retardant face paper and the second flame-retardant face paper respectively. After pressing, drying, shaping and humidification, the flame-retardant corrugated paper is obtained.

9. The method for preparing flame-retardant corrugated paper according to claim 8, characterized in that, In step S2, the amount of cationic starch added is 0.5-2.5 wt% of the oven-dry fiber mass, the amount of polyamide epichlorohydrin resin added is 0.2-1.5 wt% of the oven-dry fiber mass, and the sizing agent is one or more of alkyl ketene dimer, alkenyl succinic anhydride, or rosin gum, and the amount of the sizing agent added is 0.05-0.50 wt% of the oven-dry fiber mass.

10. The method for preparing flame-retardant corrugated paper according to claim 8, characterized in that, In step S4, the hot air drying temperature is 80-130℃ and the drying time is 20-180s; in step S6, the corrugated roll temperature is 140-190℃ and the pressing pressure is 0.2-0.8MPa. After drying and shaping, the obtained flame-retardant corrugated paper is conditioned at a temperature of 20-30℃ and a relative humidity of 45-65% for 12-48h.